STUDI GENDER DAN TANTANGAN PEREMPUAN DALAM MEWUJUDKAN MODERASI AGAMA DI INDONESIA - Ema Papuana Tekerop; Rina Elisabeth, Dea, Ayut Nursusanti, Sarmauli (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Gender studies and women's challenges in realizing religious moderation in Indonesia. This qualitative research method uses library, book and journal data as well as theories from other sources such as articles and previous research using text interaction methods or data obtained that is already available and can be used directly. Secondary data is library data which is a source that comes from other research. This method is used to make it easier to find accurate information and data in various relevant sources. This method is not limited by space or time, the research is bound by a geographic location or time. It can access information from various eras and places. Gender studies can explore the role of women in religious moderation and the challenges they face to achieve a goal, thus women have enormous potential and opportunities in maintaining the diversity that exists in Indonesia, namely other socio-cultural cultures, but this potential has not been used properly and maximum. This is because women still experience gender injustice in both the domestic and public spheres. The results of this research show that although women still experience gender injustice, but there are obstacles, many women are still innovating and collaborating in any field, including religious moderation initiatives in Indonesia. Gender studies focuses on an interdisciplinary field that interacts in complex ways with markers of identity other than sexual, national and religious. Gender, femininity and masculinity is a social organization that often does not go unnoticed. Moderation itself in Latin is moderatio which means neither more nor less, meaning equal